Positive predictive value of Birads IV Lesions on mammogram in detection of breast carcinoma - Rahim, Anila; Amjad Sattar; Syed Omair Adil; Sohail Ahmed Khan (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the positive predictive value of Breast Imaging Reporting and Data System category IV lesions, and to evaluate interobserver agreement among radiologists in interpreting the subcategories. Method: The cross-sectional study was conducted at the Dow Institute of Radiology, Dow University of Health Sciences, Karachi, from September 2018 to February 2019, and comprised adult females aged 30-60 years diagnosed with Breast Imaging Reporting and Data System IV. Already diagnosed breast carcinoma patients were excluded. The positive predictive value of Breast Imaging Reporting and Data System category IV was calculated using histopathology findings as the gold standard. Data was analysed using SPSS 22. Results: There were 191 patients with a mean age of 49.01±11.79 years. Positive family history of breast cancer was found in 33(17.3%) subjects. Category IV-A was noted in 53(28.0%) subjects, IV-B in 45(23.6%) and IV-C in 93(48.7%). The overall positive predictive value of category IV was 151(79.1%), IV-A 27(50.9%), IV-B 35(77.7%) and IV-C 89(95.6%). Malignant disease was significantly associated with architectural distortion and suspicious microcalcifications (p<0.001). A good agreement was observed in the categorisation of Breast Imaging Reporting and Data System category IV between observers 1 and 2 (kappa 0.85, 95% confidence interval: 0.70-0.99), between observers 1 and 3 (kappa 0.77, 95% confidence interval: 0.61-0.94), and between observers 2 and 3 (kappa 0.63, 95% confidence interval: 0.43-0.83). Conclusion: Breast Imaging Reporting and Data System BI-RADS IV was found to have a high positive predictive value in the diagnosis of breast cancer. Besides the interobserver agreement in terms of interpretation was good. Key Words: BIRADS IV, Interobserver agreement, Positive predicted value.